Expanding the clinical spectrum of recessive truncating mutations of KLHL7 to a Bohring-Opitz-like phenotype. Issue 12 (26th October 2017) - Bruel, Ange-Line; Bigoni, Stefania; Kennedy, Joanna; Whiteford, Margo; Buxton, Chris; Parmeggiani, Giulia; Wherlock, Matt; Woodward, Geoff; Greenslade, Mark; Williams, Maggie; St-Onge, Judith; Ferlini, Alessandra; et al.
Abstract : Background: Bohring-Opitz syndrome (BOS) is a rare genetic disorder characterised by a recognisable craniofacial appearance and a typical 'BOS' posture. BOS is caused by sporadic mutations of ASXL1 . However, several typical patients with BOS have no molecular diagnosis, suggesting clinical and genetic heterogeneity. Objectives: To expand the phenotypical spectrum of autosomal recessive variants of KLHL7, reported as causing Crisponi syndrome/cold-induced sweating syndrome type 1 (CS/CISS1)-like syndrome. Methods: We performed whole-exome sequencing in two families with a suspected recessive mode of inheritance. We used the Matchmaker Exchange initiative to identify additional patients. Results: Here, we report six patients with microcephaly, facial dysmorphism, including exophthalmos, nevus flammeus of the glabella and joint contractures with a suspected BOS posture in five out of six patients. We identified autosomal recessive truncating mutations in the KLHL7 gene. KLHL7 encodes a BTB–kelch protein implicated in the cell cycle and in protein degradation by the ubiquitin–proteasome pathway. Recently, biallelic mutations in the KLHL7 gene were reported in four families and associated with CS/CISS1, characterised by clinical features overlapping with our patients. Conclusion: We have expanded the clinical spectrum of KLHL7 autosomal recessive variants by describing a syndrome with features overlapping CS/CISS1 and BOS.